In vitro and in vivo tenocyte-protective effectiveness of dehydroepiandrosterone against high glucose-induced oxidative stress - Mukohara, Shintaro (BMC Musculoskelet Disord, 2021)
BACKGROUND: Dehydroepiandrosterone (DHEA), an adrenal steroid, has a protective role against diabetes. This study aimed to investigate the in vitro and in vivo protective effects of DHEA against high glucose-induced oxidative stress in tenocytes and tendons. METHODS: Tenocytes from normal Sprague-Dawley rats were cultured in low-glucose (LG) or high-glucose (HG) medium with or without DHEA. The experimental groups were: control group (LG without DHEA), LG with DHEA, HG without DHEA, and HG with DHEA. Reactive oxygen species (ROS) production, apoptosis, and messenger RNA (mRNA) expression of NADPH oxidase (NOX) 1 and 4, and interleukin-6 (IL-6) were determined. Further, diabetic rats were divided into a control group and a DHEA-injected group (DHEA group). NOX1 and NOX4 protein expression and mRNA expression of NOX1, NOX4, IL-6, matrix metalloproteinase (MMP)-2, tissue inhibitors of matrix metalloproteinase (TIMP)-2, and type I and III collagens in the Achilles tendon were determined. RESULTS: In rat tenocytes, DHEA decreased the expression of NOX1 and IL-6, ROS accumulation, and apoptotic cells. In the diabetic rat Achilles tendon, NOX1 protein expression and mRNA expression of NOX1, IL-6, MMP-2, TIMP-2, and type III collagen were significantly lower while type I collagen expression was significantly higher in the DHEA group than in the control group. CONCLUSIONS: DHEA showed antioxidant and anti-inflammatory effects both in vitro and in vivo. Moreover, DHEA improved tendon matrix synthesis and turnover, which are affected by hyperglycemic conditions. DHEA is a potential preventive drug for diabetic tendinopathy.